Illusory movements of the contralesional hand in patients with body image disorders - Zampini, M (BMJ Group, 2004)
Methods: Ten RBD patients (three with disorders of bodily representations) were asked to report whether movements of their right hand induced any illusory somatic or motor sensations. Inquiries on anomalous sensation of movement of the left hand were carried out while subjects: 1) observed the moving hand in a mirror propped vertically along the parasagittal plane; 2) looked directly at the moving hand; 3) looked at the still hand; 4) kept their eyes closed. Twelve healthy subjects served as controls. Results: Movement of the right hand induced a very clear sensation of movement of the left, contralesional hand in two patients affected by body image disorders. Remarkably, this occurred mainly while subjects were looking in the mirror, that is, when conflicts between visual, somatic, and motor information were maximal. In no condition did control subjects report any consistent anomalous evoked movement or sensation. Conclusions: Illusory movements of the left, plegic hand contingent upon sensorimotor conflicts can be evoked in brain damaged patients with body image disorders.